IMPLEMENTATION OF PID CONTROLLER IN CASCADE MODE FOR LEVEL CONTROL OF A TWO-TANK SYSTEM - MOHAMAD ARIFIN, NORHASHIMAH LAlLI (Universiti Teknologi Petronas, 2009)
This report discusses the approach used in level controlling of two-tank system. The controller that will be used for this implementation is cascaded PID Controller. The equipments that involve in this project are Mobile Pilot Plant and cascaded PID controller. The controller that will be used is Y okogawa Controller YS 170; dual loop programmable controller. Details on the controller is been discussed in this report. The purpose of this project is to improve the efficiency of level control for two tank system by implementing the system in cascade mode rather than in single-loop mode. The level inside the plant cannot be controlled because the plant is meant to control the flow rate of the fluid. External level controller will be attached to the plant for controlling the level of fluid inside the tank. Study on the wiring diagram of the Mobile Pilot Plant is required to trace the correct path for connection of external level controller (Y okogawa YS 170) to the pilot plant. Besides that, the study on the wiring diagram of the pilot plant is to understand the signal transmission from the field to the control panel. For Mobile Pilot Plant, the level measurement is zero-level type. The position of the transmitter and the tank is at equal zero level. Experiments in single-loop mode had been done and PI Mode Controller gave the best performance. Single-loop mode and cascade mode's performance will be compared. The configuration for cascade mode is still under testing. A lot of study has been done regarding Yokogawa controller and operation for cascade mode. Besides that, some learns on regarding level measurement and the basic concept to the implement the PID controller for this project also been done.